Genome editing and selection based on genes associated with sports athletic performance some bio-ethical issues - Zajc Petranović, Matea; Erhardt, Julija; Škerbić, Matija Mato; Jermen, Nataša; Korać, Petra (2020)
In 2003 the final results of the Human Genome Project revealed the details of our genome: a set of information about how human beings look, how we act, feel, think and develop. Soon after, other global collaborations such as the HapMap project and 1000 Genomes Project were conducted. Although the main focus was to investigate the variability in human populations and the possible connections of certain variations to different conditions and diseases, these projects also had a great impact on the understanding of the genetic influence on sports performance. In parallel, improved methods for gene analysis and gene editing were developed. Based on those methods, it became possible to detect candidate genes responsible for different performance phenotypes and develop protocols similar to gene therapies for performance enhancement in athletes. This review covers developments in genetics, the overview of candidate genes associated with athletic performance, and ethical dilemmas related to the modification of genome for sport performance enhancement.
Projekt ljudskoga genoma završen je 2003. godine, a njegovi su rezultati otkrili dotada nepoznate detalje o našem genomu: skupinu informacija o tome kako ljudska bića izgledaju, kako djeluju, osjećaju, misle i razvijaju se. Uskoro su ostvarene i druge međunarodne suradnje poput projekta HapMap i Projekta 1000 genoma. Unatoč tomu što su primarno bili usmjereni na istraživanje varijabilnosti u ljudskoj populaciji, kao i moguće povezanosti različitih varijacija s različitim stanjima i bolestima, ti su projekti također znatno utjecali na razumijevanje utjecaja gena na sportski uspjeh. Usporedno su razvijene poboljšane metode genske analize i genskoga preinačavanja na temelju kojih je postalo moguće utvrditi kandidatske gene odgovorne za različite fenotipe uspješnosti u sportu te razviti protokole slične genskim terapijama za poboljšanje sportskih natjecateljskih performansi sportaša. Ovaj rad daje pregled razvoja u genetici, pregled kandidatskih gena povezanih sa sportskim natjecateljskim performansama te etičke dvojbe vezane uz preinačavanje genoma radi poboljšavanja sportskih natjecateljskih performansi.
Im Jahr 2003 enthüllten die endgültigen Ergebnisse des Humangenomprojekts die Details unseres Genoms: Eine Reihe von Informationen darüber, wie Menschen aussehen, wie wir handeln, fühlen, denken und uns entwickeln. Bald darauf wurden weitere weltweite Kooperationen wie das HapMap-Projekt und das 1000-Genome-Projekt in die Tat umgesetzt. Obgleich das Hauptaugenmerk auf der Variabilität der menschlichen Population und den möglichen Verquickungen bestimmter Variationen mit verschiedenen Zuständen und Krankheiten lag, übten diese Projekte auch eine große Wirkung auf das Verständnis des genetischen Einflusses auf die sportliche Leistung aus. Parallel dazu wurden verbesserte Methoden zur Genanalyse und Genbearbeitung entwickelt. Basierend auf diesen Methoden wurde es machbar, Kandidatengene zu detektieren, die für verschiedene Leistungsphänotypen verantwortlich sind, und Protokolle zu entwickeln, die Gentherapien zur Leistungssteigerung bei Sportlern ähneln. Dieser Aufsatz behandelt Entwicklungen in der Genetik, den Überblick über Kandidatengene im Zusammenhang mit sportlicher Leistung und ethische Dilemmata bezüglich der Modifizierung des Genoms zur Steigerung der sportlichen Leistung.
En 2003, les résultats finaux du Projet génome humain ont révélé les détails sur la structure de notre génome : un ensemble d’informations sur l’apparence physique de l’être humain, sur sa manière d’agir, de sentir, de penser, et de se développer. Peu de temps après, d’autres collaborations mondiales telles que le projet HapMap et le projet 1000 Genomes ont été menées à terme. Axés essentiellement sur la variabilité de la population humaine et sur les possibles liens de certaines variations avec différents états et maladies, ces projets ont toutefois eu un important impact sur notre manière de comprendre l’influence que les gènes exercent sur la performance sportive. En parallèle, des méthodes améliorées pour l’analyse du gène et la modification du gène ont été développées. Il est devenu possible sur la base de ces méthodes de détecter les gènes candidats responsables des différents phénotypes associés à la performance et de développer des protocoles similaires aux thérapies géniques afin d’améliorer les performances chez les athlètes. Cet article passe en revue les développements en génétique, donne un aperçu général des gènes candidats associés à la performance athlétique et des dilemmes éthiques liés à la modification du génome dans le but d’améliorer la performance sportive.
Bibliografske bilješke uz tekst ; bibliografija: str. 335-339.
Abstract ; Sažetak ; Zusammenfassung ; Résumé.
Keywords: Sport -- Sportska uspješnost -- Sekvenciranje gena -- Geni -- Etičke dileme